Novel mosaic SRY gene deletions in three newborn males with variable genitourinary malformations. Issue 9 (28th July 2018) - Roberts, Jennifer; Lyalin, Dmitry; Tosatto, Norwood; Rana, Pratibha; Fadoul, Hiba; Welsh, Holly; Zhang, Lei; Cooley, Linda; Repnikova, Elena
Abstract : Ambiguous genitalia in the newborn can present a diagnostic challenge in medical practice. In most cases, the causes of genitourinary anomalies are not well understood; both genetic and environmental factors are thought to play a role. In this study, we report mosaic SRY gene deletion identified by fluorescence in situ hybridization (FISH) analysis in three unrelated newborn male patients with genital anomalies. G‐banded chromosomes and microarray analysis were normal for all three patients. One patient had microphallus, hypospadias, bifid scrotum, exstrophic perineal tissue identified as a rectal duplication, lumbar vertebral anomalies, scoliosis, and a dysmorphic sacrum. The other two patients had isolated epispadias with the urethral meatus close to the penopubic junction. All three had bilateral palpable gonads in the scrotum. While this is the first report of mosaic SRY deletions, mosaic SRY sequence variants have been described in patients with variable genitourinary anomalies. This study identifies FISH analysis as a reliable method for mosaic SRY deletion detection. We suggest SRY FISH analysis should be used in the clinical workup of patients with genitourinary ambiguity.